A Deep Intelligent Hybrid Intrusion Detection Framework with LIME - Ashar Ahmed Fazal (International Journal for Electronic Crime Investigation, 2024)
Network security has grown to be a major issue as a result of the development of Internet of Things (IoT) devices. Attacks known as Distributed Denial of Service (DDoS) can overwhelm and impair networks. In order to identify DDoS and other network intrusion threats in real-time, accurately, and with justification, this study suggests a unique deep learning-driven fog computing architecture named as Deep Intelligent Hybrid Intrusion Detection Framework with LIME (DIHIF-LIME). The main advancement is the creation of a hybrid intrusion detection system that integrates randomness measurements taken from network traffic with a K-Nearest Neighbor (KNN) machine learning classifier. The justification for predictions is explained using Local Interpretable Model-Agnostic Explanations (LIME), which promotes explainability. Using datasets including network assaults, Long-Short-Term Memory (LSTM) neural networks are created and compared. Utilizing 5-fold cross-validation, LSTM outperformed benchmarks with the maximum accuracy of 99.97%. In conclusion, the proposed fog computing intrusion detection framework with LIME explainability offers a rapid, precise, scalable, and interpretable end-to-end solution from IoT devices to the cloud. A thorough test shows that the method is effective in protecting IoT networks from DDoS and other assaults. The two main advances that are presented are hybrid detection and LIME explainability.